Eating behavior, body dissatisfaction and orthorexia nervosa: a review of the relationship between these factors (Research, Society and Development, 2023)
Objective: The present study carried out a systematic review with the objective of investigating factors related to eating behavior, body dissatisfaction and orthorexia nervosa in university students. Methods: We analyzed 26 articles available in the LILACS, SciELO and Pubmed databases, covering studies published between 2012 and 2023. Results: The results revealed a high prevalence of orthorexia nervosa among university students, especially in women and students of the nutrition course. Furthermore, students with high body dissatisfaction will present less physical activity and greater dietary restrictions. Conclusion: Based on the information presented, I conclude that it is essential to implement preventive interventions to deal with the psychosocial risks associated with orthorexia nervosa. It is also highlighted the need to develop a specific and valid questionnaire for the diagnosis and evaluation of the condition, as well as the performance of longitudinal and prospective studies to deepen the understanding of the prevalence and risk factors of orthorexia nervosa in the student population.